(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Introduction: Hand is specialized organ of the body performing complex functions, and it enables a person to earn his livelihood. Various options are there for treatment of metacarpal shaft fractures, in this study we treated patients with cerclage wiring and noted its outcomes. Material and methods: patients who were presented with oblique/spiral fracture of shaft of metacarpal during the study period were treated with cerclage wiring and followed until they were able to return to work. Results: seven patients with eight fractures were treated during the study period. Reduction achieved was good in all patients. We had one late complication of wire breakage and no malunion or non-union occurred. Conclusion: we conclude that cerclage wiring treatment is effective method for treatment of oblique/spiral fracture of metacarpals and a viable and cheap alternative to plate and screw method in low socio-economic patients.